Evaluation of metformin treatment in patient with polycystic ovary syndrome in Kirkuk city - Mohammed Al-jaf, Thulfiqar Abdulla; AL-Mandalawi, Sanaa; Sabah, Iman; Azzo, Emil Nasir; Gassan, Ibaa; qadir, Nazhet Abdul (Zanco Journal of Medical Sciences (ZJMS), 2012)
Background and objectives: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women of fertile age, affecting 5-10% of the female population. The aim of the present study is to evaluate the endocrine and metabolic effects of metformin in patients with polycystic ovary syndrome in Kirkuk city. Methods: Eighty female with polycystic ovary syndrome (PCOS), were classified in to two groups, the first group ,who received Clomifene citrate and Metformin hydrochloride included 45 patients and the second group , who received Clomifene citrate only (control group) included 35 patients. All study patients, were diagnosed as polycystic ovary syndrome and they were on treatment at least two months before blood sample collection. Laboratory assessment that obtained included serum, free testosterone, leptin and insulin glucose and lipid profile. Results: No significant differences in median of, serum insulin, insulin resistance or serum leptin between study groups were observed. The median free serum testosterone was significantly lower (23 pg/ml) in those treated with metformin compared to those on ordinary treatment (50 pg/ml). Fasting serum glucose, HDL – cholesterol and total cholesterol were significantly higher in group without metformin (116.2 , 41.3 , 161.8 mg/dL respectively) compaired to group with metformin (101.5, 34.3 , 138.8 mg/dL respectively). The remaining biomarkers (serum LDL-cholesterol, serum VLDL-cholesterol and triglyceride) showed no statistically significant differences between two groups. We conclude that metformin treatment has beneficial effects on serum, free testosterone cholesterol and glucose in obese women with PCOS.